The Addams family : the complete first volume [videorecording (DVD)] - Addams, Charles, 1912-1988; Levy, David, 1913-2000; Astin, John; Jones, Carolyn, 1930-1983; Cassidy, Ted; Coogan, Jackie, 1914-1984; Weatherwax, Ken, 1955-2014; Loring, Lisa (Distributed by Twentieth Century Fox Home Entertainment, 2006)
Join Gomez, Morticia, Uncle Fester, Lurch, Cousin Itt and the rest of the gang for a fiendishly funny and altogether ooky experience.